2020
DOI: 10.3390/atmos11040370
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality: A Focus on the European Legislation and State-of-the-Art Research in Italy

Abstract: The World Health Organization (WHO) has always stressed the importance of indoor air quality (IAQ) and the potential danger of pollutants emitted from indoor sources; thus, it has become one of the main determinants for health. In recent years, reference documents and guidelines have been produced on many pollutants in order to: i) decrease their impact on human health (as well as the number of pollutants present in indoor environments), and ii) regulate the relevant levels of chemicals that can be emitted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…It is reasonable to think that the different cleaning products used in the different schools are responsible for the high PM 2.5 levels as well as for the high levels of some gaseous pollutants. Further, the formaldehyde levels are quite interesting: although they could appear high, they are below the WHO guideline values [ 9 ] (100 µg m −3 ). Its levels were above the guideline value (113.6, 115.8 and 165.2 µg m −3 ) only in three situations (two classes in school #D and 1 in school #F, respectively), due to smoking by cleaning staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to think that the different cleaning products used in the different schools are responsible for the high PM 2.5 levels as well as for the high levels of some gaseous pollutants. Further, the formaldehyde levels are quite interesting: although they could appear high, they are below the WHO guideline values [ 9 ] (100 µg m −3 ). Its levels were above the guideline value (113.6, 115.8 and 165.2 µg m −3 ) only in three situations (two classes in school #D and 1 in school #F, respectively), due to smoking by cleaning staff.…”
Section: Discussionmentioning
confidence: 99%
“…The indoor environment therefore contributes significantly to the exposure to pollutants, many of which have a higher concentration indoors than outdoors [ 5 ]. Due to the high number of emission sources that can be identified in confined environments and the consequent high concentration of pollutants, indoor pollution is therefore considered an extremely complex and difficult to control form of pollution [ 6 , 7 , 8 , 9 , 10 ]. An increasing number of studies have confirmed that exposure to indoor pollutants causes a greater risk of respiratory disorders, probably consequent to a marked inflammation of the airways, which underlies oxidative stress mechanisms [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…VOCs are produced in large amounts in the transport sector, and they are common ingredients of many cleaning products, representing one of the major sources of air pollutants [ 81 , 82 ]. Reduction of VOCs emission represents a priority, and it has been considered mandatory by several national and international normative [ 83 ].…”
Section: Deep Eutectic Solvents For Gas Solubilizationmentioning
confidence: 99%
“…Despite increasing public health concern related to the indoor air quality due to the amount of time that people spend indoor during the day, specific reference directives are lacking in the European legislation. The subject is rather regulated by prelegislative initiatives, i.e., specific documents elaborated by national or European working groups (Kurt-Karakus 2012; Settimo et al 2020). In these initiatives, indoor pollution monitoring often coincides with workplace air quality.…”
Section: The Indoor Environmentmentioning
confidence: 99%